2007
DOI: 10.1016/j.biochi.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prehibernation and hibernation effects on the d-3-hydroxybutyrate dehydrogenase of the heavy and light mitochondria from liver jerboa (Jaculus orientalis) and related metabolism

Abstract: Kebbaj To cite this version:Driss Mountassif, Mostafa Kabine, Norbert Latruffe, M'Hammed Saïd El Kebbaj. Prehibernation and hibernation effects on the D-3-hydroxybutyrate dehydrogenase of the heavy and light mitochondria from liver jerboa (Jaculus orientalis) and related metabolism.. Biochimie, Elsevier, 2007, 89 (8) Abstract:The D-3-hydroxybutyrate dehydrogenase (BDH) (EC 1.1.1.30) from liver jerboa (Jaculus orientalis), a ketone body converting enzyme in mitochondria, in two populations of mitochondria (hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…They may also play a role in combating oxidative stress during arousal when oxygen levels and oxygen consumption rise dramatically over short periods of time as animals power themselves back to euthermia by means of high rates of lipid-fueled thermogenesis in BAT and skeletal muscle. Indeed, recent studies have shown that elevated levels of biliverdin or bilirubin are associated with hibernation: plasma bilirubin rose 5-fold in torpid jerboas (Mountassif et al 2007), and bilirubin levels increased 5-fold in bile in hibernating ground squirrels (Baker and van Breukelen 2009). Compared with squirrels entering hibernation or in full torpor, biliverdin in ground squirrel liver was 15-to 20-fold higher both during arousal (Tb 20-25 8C) and during the interbout periods before animals re-entered torpor (>2 h at Tb >34 8C) (Nelson et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They may also play a role in combating oxidative stress during arousal when oxygen levels and oxygen consumption rise dramatically over short periods of time as animals power themselves back to euthermia by means of high rates of lipid-fueled thermogenesis in BAT and skeletal muscle. Indeed, recent studies have shown that elevated levels of biliverdin or bilirubin are associated with hibernation: plasma bilirubin rose 5-fold in torpid jerboas (Mountassif et al 2007), and bilirubin levels increased 5-fold in bile in hibernating ground squirrels (Baker and van Breukelen 2009). Compared with squirrels entering hibernation or in full torpor, biliverdin in ground squirrel liver was 15-to 20-fold higher both during arousal (Tb 20-25 8C) and during the interbout periods before animals re-entered torpor (>2 h at Tb >34 8C) (Nelson et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The rise in hepatic biliverdin levels in IBA squirrels may therefore reflect a burst of heme degradation as the liver is reperfused with blood upon arousal. Although there is little information on heme metabolism in hibernators, plasma bilirubin levels are elevated in torpid jerboas (35). Increased biliverdin during arousal may have functional significance beyond just heme catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that lipids play crucial roles in hibernation biology through their contribution to energy metabolism during the winter fast and their effects on membrane composition, which have been linked to torpor patterns [3], [4], [5], [6], [7]. Less well understood is the effect of hibernation on lipid trafficking, especially cholesterol and lipoprotein dynamics, over the annual cycle and its functional significance [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%